Comparison data of a two-target real-time PCR assay with and without an internal control in detecting Salmonella enterica from cattle lymph nodes - Jianfa Bai; Valentina Trinetta; Xiaorong Shi; Lance W. Noll; Gabriela Magossi; Wanglong Zheng; Elizabeth P. Porter; Natalia Cernicchiaro; David G. Renter; Tiruvoor G. Nagaraja (Data in Brief, 2018)
A real-time PCR (qPCR) assay targeting on invA and pagC genes was developed and validated for the detection and quantification of Salmonella enterica strains (Bai et al., 2018) [1]. A host gene, normally an endogenous housekeeping gene (Beer-Davidson et al., 2018; Poon et al., 2004) [2,3], or an irrelevant exogenous gene (Cheng et al., 2015; Sedlak et al., 2014) [4,5] has been widely used as an internal control to monitor nucleic acid extraction efficiencies and potential PCR inhibitions in PCR-based detection assays. An endogenous internal control designed based on the 18S rRNA gene was used in the above-mentioned qPCR assay. This 18S rRNA internal control amplifies the target gene in multiple species including bovine, swine, ovine, caprine and cervine. Data was generated by the duplex qPCR assay on 138 enriched cattle lymph node samples without the internal control, and compared with data on the same samples tested by the triplex qPCR assay that has the 18S rRNA gene as internal control. Threshold cycle (Ct) data for the duplex and the triplex qPCR on the 138 samples were similar, and are presented in this brief report. Keywords: Real-time PCR, Threshold cycle, Internal control, Salmonella, Foodborne pathogen, Lymph node